Pharmacodynamics of Piroxicam from Novel Solid Lipid Microparticles Formulated with Homolipids from Bos indicus - O. Nnamani, Petra; A. Attama, Anthony; C. Kenechukwu, Franklin; C. Ibezim, Emmanuel; U. Adikwu, Michael (Current Drug Delivery, 2013)
The dissolution of piroxicam is a limiting step in its bioavailability on account of its hydrophobicity. The objective of this research was to formulate novel solid lipid microparticles (SLMs) based on homolipids (admixtures of tallow fat (TF) and Softisan® 142 (SFT) templated with Phospholipon® 90G (P90G), a heterolipid for the delivery of piroxicam. Lipid matrices consisting of TF and SFT in ratios of 1:1, 1:2 and 2:1 were templated with the heterolipid, P90G and characterized by differential scanning calorimetry (DSC). The SLMs produced by hot homogenization technique using the matrices were characterized in terms of thermal properties, particle size, morphology, drug encapsulation efficiency, stability studies and in vitro diffusion studies. In vivo pharmacodynamic study was performed using egg albumin- induced pedal edema in rats. The results showed that addition of Softisan® 142 improved the drug holding capacity of the micellar solution of 2:1 mixture of TF and SFT. The in vitro diffusion of piroxicam from this SLM showed maximum release of 87.53 % and followed non-Fickian diffusion kinetic mechanism. At dose equivalence of 10 mg, piroxicamloaded SLMs showed superior in vivo anti-inflammatory properties at 3 h than Feldene® and the pure drug sample. This study has shown that surface-modified SLMs could confer favourable properties with respect to drug release and antiinflammatory activity on SLMs for the delivery of piroxicam, thus encouraging further development of the formulations.
Keywords: Bos indicus